Anthropometric Methods for the Reduction of Accidents Due to Musculoskeletal Disorders in a Company of the Industrial Sector - Andia-Fernandez, Jose Fernando (2022)
Currently there are several methods and tools that allow us to know if a worker is at risk of suffering from a musculoskeletal disorder (MSD). Which can affect the physical integrity of people in a short or long term. However, many industrial companies have neglected the importance of the human factor and focus solely on the fulfillment of production. For this reason, the objective of this study is to investigate those positions in different areas of an industrial plant dedicated to the manufacture of plastic derivative products that may cause a muscle injury to workers or a disabling accident. Which does not only affect the person, but also the company. Due to the days of medical rest that the staff will have to need for their recovery and that the company must cover with the hiring of overtime or additional staff to meet the demand. The methods used for the evaluation of the activities will be Ovako Working Analysis System (OWAS), on the one hand, and National Institute of Occupational Safety and Health (NIOSH) on the other. It is worth mentioning that, once the analysis with these ergonomic tools is completed, possible solutions will be sought with the anthropometric technique. Which stands out, because it allows the work environment to adapt to the needs of the operators and not the other way around.